Microbial bioelectrosynthesis of hydrogen: Current challenges and scale-up - Kitching, Michael; Butler, Robin; Marsili, Enrico (Enzyme and microbial technology, 2017)
•Bioelectrosynthesis is a promising technology for industrial production of H2.•Bottlenecks include slow kinetics and consumption of hydrogen in the biofilm.•Bioelectrosynthesis of H2 from complex feedstocks is feasible with mixed biofilms. Sustainable energy supplies are needed to supplement and eventually replace fossil fuels. Molecular hydrogen H2 is a clean burning, high-energy fuel that is also used as reducing gas in industrial processes. H2 is mainly synthesized by steam reforming of natural gas, a non-renewable fuel. There are biosynthetic strategies for H2 production; however, they are associated with poor yield and have high cost. The application of an electrochemical driving force in a microbial electrolysis cell (MEC) improves the yield of biological reactions. The performance of the MEC is influenced by experimental parameters such as the electrode material, reactor design, microbial consortia and the substrate. In this review, factors that affect the performance of MECs are discussed and critically analysed. The potential for scale-up of H2 bioelectrosynthesis is also discussed.